CONSTITUTIONAL RIGHT TO HOUSING FOR POOR PEOPLE IN INDONESIA - Erwiningsih, Winahyu; Ali, Mahrus (RADJA PUBLIKA, 2023)
Many poor people in Yogyakarta lack proper housing as well as adequate government assistance and facilities. Therefore, this study aimed to develop a legal framework for fulfilling the constitutional right to housing for the poor by a) discovering the principles underlying the constitutional right to housing for the poor, b) elaborating on the laws and regulations on the matter, and c) finding the reality of implementation in Yogyakarta. This normative legal study was conducted using a philosophical dogmatic analysis with a statutory regulation approach. The results showed that 1) the arrangement of constitutional rights to housing for the poor was based on a rule of law, protection of human rights, and social justice. These principles prioritized non-discrimination to lead a decent life, which required proper assistance and accommodation. 2) The constitutional right to housing for the poor had not been fully accommodated by laws and regional regulations in Yogyakarta. 3) During the study period, the poor could only receive housing repair assistance suggested by local citizens. These findings implied that the central and regional governments should make regulations which accommodate the housing needs of all citizens. Additionally, technical matters and substance content should be regulated in line with the 1945 Constitution and Pancasila as the soul of the nation to fulfill the constitutional rights of the poor.